Investigating the Perceptions of Intellectual Diversity Among Socially Conservative Christian Seniors at Elite U.S. Colleges. Issue 1 (2nd January 2016) - Brow, Mark V.
ABSTRACT: This study investigated the perceptions of intellectual diversity at elite U.S. universities through the lens of the socially conservative Christian senior. Closely aligned with the principle of academic freedom, intellectual diversity is a foundational value putatively espoused by most if not all colleges and universities in the US. Although studies have consistently shown a professorate that is overwhelmingly Democratic and ideologically left-of-center, many scholars deny that any systematic bias exists. Research has shown a correlation between commitment to Christian/conservative values and perception of professor bias. Using hierarchical generalized linear modeling (HGLM) on a subset of the nationally representative sample ( N  = 2, 789) of "very high" institutions, this current study found corroborative evidence that socially conservative Christian students were disproportionately "dissatisfied" or "very dissatisfied" with their institutions' respect for the expression of diverse beliefs. Generalized findings suggest that systematic bias vis-à-vis the expression of diverse beliefs exists at elite U.S. colleges. The discussion begins by situating intellectual diversity within its historical and contemporary contexts.